2014
DOI: 10.1371/journal.pgen.1004861
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Mitochondrial Polyubiquitin by PINK1 Promotes Parkin Mitochondrial Tethering

Abstract: The kinase PINK1 and the E3 ubiquitin (Ub) ligase Parkin participate in mitochondrial quality control. The phosphorylation of Ser65 in Parkin's ubiquitin-like (UBl) domain by PINK1 stimulates Parkin activation and translocation to damaged mitochondria, which induces mitophagy generating polyUb chain. However, Parkin Ser65 phosphorylation is insufficient for Parkin mitochondrial translocation. Here we report that Ser65 in polyUb chain is also phosphorylated by PINK1, and that phosphorylated polyUb chain on mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(134 citation statements)
references
References 52 publications
5
127
0
Order By: Relevance
“…The MMP is an indicator of the mitochondrial functional status, and deregulation of MMP leads to a large spectrum of major human diseases, including diabetes, neurodegeneration, cancer and others (52). It has been reported that MB maintains the MMP when mitochondria are dysfunctional (2), and the MMP is a regulator of mitophagy (27). Accordingly, we investigated the effect of MB on the MMP and the relationship between the MMP and the induction of mitophagy.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The MMP is an indicator of the mitochondrial functional status, and deregulation of MMP leads to a large spectrum of major human diseases, including diabetes, neurodegeneration, cancer and others (52). It has been reported that MB maintains the MMP when mitochondria are dysfunctional (2), and the MMP is a regulator of mitophagy (27). Accordingly, we investigated the effect of MB on the MMP and the relationship between the MMP and the induction of mitophagy.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, mitophagy plays a crucial role in controlling the quality of mitochondria by preventing the generation of ROS by dysfunctional mitochondria (24,25). Deficiency in mitophagy is associated with neurodegenerative diseases such as Parkinson's disease (26,27), Alzheimer's disease (28,29) and Huntington's disease (30). Stroke is another type of neurodegenerative disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the differential effects of various types of Ub chains on mitophagy, a further layer of complexity is added by the potential for these chains to be phosphorylated by PINK1 (Shiba-Fukushima et al 2014a;Okatsu et al 2015b;Wauer et al 2015). The functional consequences of PINK1-mediated Ub chain phosphorylation are currently unknown.…”
Section: Phosphorylation and Its Effect On Dub Activitymentioning
confidence: 99%
“…Hence, the work conducted both in mammalian neurons and in flies, suggests that dysfunctional mitochondria fail to be transported in the cell. Stabilized Pink1 also targets other proteins: it recruits and phosphorylates Parkin (Shiba-Fukushima et al, 2012) and ubiquitin (Kane et al, 2014;Kazlauskaite et al, 2014;Koyano et al, 2014;Shiba-Fukushima et al, 2014), and Parkin then ubiquitinates mitochondrial targets that tag the organelle for degradation. The evidence indicates this pathway is implicated in mitochondrial quality control, but the targets ubiquitinated by Parkin including Mitofusin (Poole et al, 2010;Ziviani et al, 2010) and VDAC (Geisler et al, 2010;D.…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%